Sustainable urban drainage systems (2014-2023) by using bibliometric analysis method / Abraham Ayuen Ngong Deng, Nursetiawan and Jazaul Ikhsan - Ngong Deng, Abraham Ayuen; -, Nursetiawan; Ikhsan, Jazaul (2024)
Sustainable urban drainage systems (SUDS) are increasingly crucial for stormwater management. This bibliometric review analyses research trends on sustainable urban drainage systems over the past decade (2014-2023) using data from Scopus. The analysis found 705 articles, 192 conference papers, 85 book chapters, and 64 reviews on sustainable urban drainage systems. Publication volume increased by 66% during the study period, indicating rising research interest. The most cited article (294 citations) was a 2019 review by Andrés-Doménech et al. on innovations in sustainable urban drainage systems. Analysis of author keywords revealed 8 clusters of research topics, with "sustainable urban drainage systems" being the dominant term with 889 keywords. Although general sustainable urban drainage system terms prevail, the use of keywords related to network visualization methods like VOS viewer is rapidly increasing. The United Kingdom published the most SUDS research (315 articles), followed by China (149), Spain (135), the United States (126), and Italy (107 articles). Research was concentrated in the environmental science and engineering fields. However, this bibliometric analysis provides insights into SUDS research trends, the most active countries and institutions, and emerging topic areas. The rapid increase in publications and use of network visualization techniques demonstrates SUDS' growing importance in urban stormwater management. The results can help inform future research directions, such as applying advanced data analytics to improve SUDS design and performance. Expanding bibliometric analyses with additional techniques like VOS viewer could further enhance understanding of this critical area of urban environmental research. Developing bibliometric methods and adding feature extraction algorithms when selecting features used to model data can increase the efficiency and accuracy of the data on sustainable urban drainage systems. The development of research data using Vos viewers images with this type of data processing research can also be maximized for research related to the sustainable urban drainage system.